2011
DOI: 10.1111/j.1556-4029.2011.01805.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Adrenaline to Noradrenaline Ratio Is a Superior Indicator of Antemortem Hypothermia Compared with Separate Catecholamine Concentrations

Abstract: The significance of urinary catecholamines and small gastric mucosal bleedings, Wischnewsky's spots, in postmortem diagnosis of hypothermia deaths was evaluated. Autopsy cases (n=358) were divided into hypothermia, suspected hypothermia, and control groups. The catecholamine levels did not correlate with the length of the postmortem period. The adrenaline to noradrenaline ratio was most effective in detecting hypothermia (68.9% sensitivity, 78.1% specificity). The median adrenaline concentrations were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 25 publications
2
28
0
Order By: Relevance
“…Error bars represent 95 % confidence interval. ***p<0.001 compared with hypothermia as main cause of death (COD); ¤p<0.05 compared with cardiovascular disease (CVD) deaths adrenaline (73.7 %) or ANR (68.9 %) [3], but the specificity of ANR was somewhat better (78.1 %). Most studies on hypothermia indicators have not provided these calculations exclusively for hypothermia deaths, making it difficult to compare the diagnostic accuracy of different indicators.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Error bars represent 95 % confidence interval. ***p<0.001 compared with hypothermia as main cause of death (COD); ¤p<0.05 compared with cardiovascular disease (CVD) deaths adrenaline (73.7 %) or ANR (68.9 %) [3], but the specificity of ANR was somewhat better (78.1 %). Most studies on hypothermia indicators have not provided these calculations exclusively for hypothermia deaths, making it difficult to compare the diagnostic accuracy of different indicators.…”
Section: Discussionmentioning
confidence: 98%
“…The adrenaline to noradrenaline ratio in urine has been shown to be a decent marker, with high (>0. 19) values referring to hypothermia [3], but there is an indisputable need for a better one.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, catecholamine stability in postmortem blood samples remains an issue of controversy, since they may diffuse from sympathetic nerve ending and adrenal glands into the blood [30].…”
Section: Discussionmentioning
confidence: 99%
“…Pakanen et al [6] analyzed urine catecholamine levels in 358 autopsy cases, including 145 cases with hypothermia as the main cause of death. They found that adrenaline was a better marker of hypothermia death than noradrenaline, as already demonstrated by Hirvonen and Huttunen [49].…”
Section: Catecholaminesmentioning
confidence: 99%
“…This makes the postmortem diagnosis of hypothermia relatively arduous in forensic death investigations [6].…”
Section: Introductionmentioning
confidence: 99%